Theoretical investigation on insulin dimer - b - cyclodextrin interactions using docking and molecular dynamics simulation - Muhammad, Erma Fatiha; Adnan, Rohana; Mohammad Latif, Muhammad Alif; Abdul Rahman, Mohd Basyaruddin (Springer Netherlands, 2016)
In our study, molecular docking and molecular dynamics (MD) simulations were performed in order to explore the interactions between human insulin and β-cyclodextrin (β-CD). Molecular docking study was performed using the Autodock v4.2 program to determine the number of β-CD molecules that adhere to the binding sites of insulin. A random structure docking approach using an initial ratio of 1:1 insulin-β-CD was conducted and from these, additional β-CDs were added. Molecular docking results revealed that a maximum of four β-CDs are able to bind to the insulin structure with the 1:3 insulin-β-CD ratio producing the lowest binding free energy. The docked conformations showed that hydrophobic interactions played a crucial role in insulin-β-CD conformational stability in addition to the formation of hydrogen bonds. A 50 ns MD simulation was further conducted using an NPT ensemble to verify the results obtained by molecular docking. The analysis of the MD simulation results of the 1:3 insulin-β-CD formation system conclude that a good interaction exists between insulin and β-CDs and the RMSD value obtained was 4.00 ± 0.50 Å. The RMSF profiles of insulin in the 1:3 insulin-β-CD formation also show reduced amino acid residues flexibility as compared to the free insulin system. The theoretical results indicated the presence of significant interactions between insulin and β-CD which could provide interesting insights into an insulin formulation.